Cremanthodium lingulatum (Asteraceae, Senecioneae) is merged with C. pseudo-oblongatum - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2017)
Critical observations on both herbarium specimens (including type material) and living plants demonstrate that Cremanthodium lingulatum and C. pseudo-oblongatum (Asteraceae, Senecioneae) are conspecific. We therefore place the former into the synonymy of the latter. Lectotypification is proposed for C. pseudo-oblongatum.